The Development of Guideline on Social Impact Management in Community from Hosting International Sport Events - Phantumabamrung, Paak; Nakpanom, Worawee (Arts of Management Journal, 2022)
This article aimed to 1) study social impacts in the community from hosting international sporting events; 2) compare the difference between the positive and negative social impacts classified by gender, age, and occupation; and 3) develop the guideline on social impact management. This research was a mixed method research employing 1) the questionnaire with a reliability value at 0.913 for quantitative research. The sample consisted of 480 residents in 8 randomly selected districts in Buriram province and used stratified random sampling. And 2) Semi-Structured Interviews for qualitative research. The data were analyzed by using descriptive and inferential statistics for the questionnaire and content analysis for the interview. The research results were found: 1) the positive social impact was at a high level, with a mean at 3.95, and the negative social impact was at a medium level, with a mean at 2.69. 2) The residents with different gender and age did not had statistically significant difference of opinion in social impacts, however the residents with different occupation had statistically significant difference of opinion in social impacts at the .05 level. And 3) guideline on social impact management in community from hosting international sporting events found that representative of residents paid attention to improve the community bond and avoid rowdy or quarrel. Therefore, identifying evaluation and response impacts was imperative for creating support for hosting sports events.